Women's lived experiences of the breast cancer trajectory: the waiting period for treatment and the impacts on feminine identity - Mulder, Anja (Gender Studies, 2014)
Breast cancer, according to research, is diagnosed in approximately one in every twenty-nine women in South Africa. Differences in gender, race and class produce disparities in health care, subjecting lower class women to lengthy waiting periods between diagnosis and treatment. Present research studies on breast cancer predominantly use quantitative methods. To understand women's lived experiences of the breast cancer trajectory this study explores experiences encountered during the waiting period, as well as the impacts of breast cancer and its treatment on feminine identity. For this a qualitative method was applied. Semistructured, in-depth interviews were conducted with five black and coloured breast cancer patients residing at two of CANSA's care homes. Participants varied in age and phases of treatment, were all married or widowed, had minor dependants, and had all travelled from distant and outlying areas. Based on a thematic analysis, six themes emerged from the data collected. These included: First experiences of cancer in the body; breast cancer and waiting periods from the patient's perspective; sources of support; meanings and perceptions of being a woman; conceptualising disease, and patients' needs. The analysis illustrates the importance of researching women's lived experiences and highlights that these need to be understood within a framework of socially constructed notions of gender, race and class in order to improve breast cancer treatment and psycho-social care.